1999
DOI: 10.1063/1.479218
|View full text |Cite
|
Sign up to set email alerts
|

Electron binding to valence and multipole states of molecules: Nitrobenzene, para- and meta-dinitrobenzenes

Abstract: Low-energy photoelectron imaging spectroscopy of nitromethane anions: Electron affinity, vibrational features, anisotropies, and the dipole-bound state J. Chem. Phys. 130, 074307 (2009); 10.1063/1.3076892Effect of excess electron and one water molecule on relative stability of the canonical and zwitterionic tautomers of glycine Nitrobenzene anions (NB Ϫ ) in both valence and dipole bound states are examined using laser ͑photodetachment͒ photoelectron and Rydberg electron transfer ͑RET͒ spectroscopies. Photoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 42 publications
4
77
3
Order By: Relevance
“…For calibration, the G3MP2B3 AEA of PhNO and PhNO 2 are 1.08 and 0.91 eV, correspondingly. The theoretical value for nitrobenzene is in reasonable agreement with photoelectron spectroscopy experiments, 1.00 ± 0.01 eV 75 .…”
Section: A Structure and Electron Density Distribution In Aromatic Nsupporting
confidence: 74%
“…For calibration, the G3MP2B3 AEA of PhNO and PhNO 2 are 1.08 and 0.91 eV, correspondingly. The theoretical value for nitrobenzene is in reasonable agreement with photoelectron spectroscopy experiments, 1.00 ± 0.01 eV 75 .…”
Section: A Structure and Electron Density Distribution In Aromatic Nsupporting
confidence: 74%
“…However this is no longer the case, as they have been found to be important in a variety of chemical processes. The demonstration that dipole-bound anions can serve as precursors to formation of valencelike anions [38][39][40] has generated much interest in their role in electron capture in biological molecules such as uracil and thymine. [41][42][43][44][45][46] In addition, many biologically important molecules can exist as zwitterions, which because of their large dipole moments, can form dipole-bound anions.…”
Section: Introductionmentioning
confidence: 99%
“…None of the unmodified proteinogenic amino acids have a positive electron affinity. However, it was shown that benzyl modifications of cysteine with an EA of Ն1.00 eV, specifically 3-nitrobenzylcysteine (EA ϭ 1.00 eV [37] and 3,5-dinitrobenzylcysteine (EA ϭ 1.65 eV [38], termed 'electron predators', inhibit peptide backbone cleavage by ECD and the related electron-transfer dissociation (ETD) completely [36]. Identical rates of electron capture were observed for doubly-charged peptides containing modifications with disparate EA suggesting initial electron capture is governed by longrange interactions, i.e., the electron is captured to high-n Rydberg states, as proposed by McLafferty [10].…”
mentioning
confidence: 99%